Potentiality of Eichhornia crassipes as partial bovine feed: A step towards managing its invasiveness (Asian Journal of Agriculture, 2024)
Abstract. Guchhait S, Paria DS, Shrestha R, Pradhan P, Roy A. 2025. Potentiality of Eichhornia crassipes as partial bovine feed: A step towards managing its invasiveness. Asian J Agric 9: 60-67. Menace of invasive species is rampant in tropical and subtropical areas and is a threat to the integrity of regional aquatic ecosystems. Bio-utilization has been suggested as one of the means of controlling the populations of invasive species. However, invasive plants such as Water Hyacinth (WH) (Eichhornia crassipes) are also known to accumulate heavy metals. From the literature survey, the young leaves of WH collected from freshwater ponds were found to have the lowest amounts of heavy metals in comparison to the roots as well as other fodder plants for bovines. This study aims to determine the effects of substituting common traditional bovine feed used in Eastern India with young leaves of the invasive plant WH collected from freshwater ponds on milk production, cow health, and its economic aspect. Eight cows aged between 3.7 to 6.7 years were considered for the study. In the control (0%) collection, they were fed with partial replacement feed composed of 5%, 10%, 15%, 20%, and 25% of total cow feed with young WH leaves. During the investigation, we assessed feed replacement-dependent changes in milk production and cow health to determine the EC50, the optimal replacement level, and the efficacy of partial feed replacement with WH. From the study, it was known that an increase in WH% in the partially replaced feed had a positive effect on milk production while it had an adverse effect on health (stomach upset). Further, replacement feed with the range of 12.19-14.89% WH (maximum 15%) was identified to be optimum in terms of both milk production, cow health, and monetary contribution from milk output. So, the idea may be considered a step towards controlling the population of WH.
Keywords: Aquatic invasive plant, bio-utilization, cow health, milk production, tolindex, TPR-FPR